Borgnakke's Fundamentals of thermodynamics - Borgnakke, C.; Sonntag, Richard Edwin (John Wiley & Sons, 2017)
Borgnakke's Fundamentals of Thermodynamics continues to offer a comprehensive and rigorous treatment of classical thermodynamics, while retaining an engineering perspective. This classic text provides a solid foundation for subsequent studies in fields such as fluid mechanics, heat transfer and statistical thermodynamics, and prepares students to effectively apply thermodynamics in the practice of engineering.